Isatuximab in combination with carfilzomib and dexamethasone in 1q21+ patients with relapsed/refractory multiple myeloma: Long-term outcomes in the Phase 3 IKEMA study - Facon, Thierry; Moreau, Philippe; Špicka, Ivan; Suzuki, Kenshi; Yong, Kwee; Mikhael, Joseph; Fukao, Taro; Bisht, Kamlesh; Armstrong, Nicole M; Macé, Sandrine; Risse, Marie-Laure; Martin, Thomas (Hematological oncology, 2024)
Gain/amplification of 1q21 (≥3 copies), a chromosomal abnormality frequently observed in multiple myeloma, can negatively affect prognosis, due to its involvement in resistance to anti-myeloma therapy and disease progression. In this updated subgroup analysis of the randomized, Phase 3 IKEMA study (NCT03275285) in relapsed/refractory multiple myeloma (RRMM), we evaluated progression-free survival (PFS) and depth of response with the anti-CD38 antibody isatuximab plus carfilzomib-dexamethasone (Isa-Kd) versus Kd, in 1q21+ patients and related subgroups, at long-term follow-up (44.2 months). Our analysis included patients with 1q21+ (≥3 copies, with/without high-risk chromosomal abnormality [HRCA]), isolated 1q21+ (≥3 copies, without HRCA), gain(1q21) (3 copies, with/without HRCA), and amp(1q21) (≥4 copies, with/without HRCA). PFS benefit was achieved with Isa-Kd versus Kd in patients with 1q21+ (HR 0.58, 95% CI: 0.37-0.92), with isolated 1q21+ (HR 0.49, 95% CI: 0.27-0.92), with gain(1q21), or amp(1q21), consistent with the overall population and prior interim 1q21+ subgroup analyses. Median PFS with Isa-Kd versus Kd was 25.8 versus 16.2 months in 1q21+ patients and 38.2 versus 16.2 months in patients with isolated 1q21+. Clinically meaningful, higher rates of very good partial response or better, complete response or better (≥CR), minimal residual disease (MRD) negativity, and MRD negativity and ≥CR were reached with Isa-Kd versus Kd in patients with 1q21+, isolated 1q21+, gain(1q21), or amp(1q21). In Isa-Kd and Kd, the MRD negativity and ≥CR rate was 29.3% versus 15.4% in 1q21+ patients, 36.2% versus 12.9% in patients with isolated 1q21+, 27.9% versus 13.5% in patients with gain(1q21), and 31.3% versus 20.0% in patients with amp(1q21), respectively. In conclusion, addition of Isa to Kd in triplet combination therapy has shown PFS benefit and deeper responses, compared with Kd, in 1q21+ patients at higher risk of progression, including patients with isolated 1q21+, gain(1q21), and amp(1q21), thus supporting Isa-Kd an effective treatment option for patients with RRMM.
Keywords: Oligopeptides; protokoly protinádorové kombinované chemoterapie; humanizované monoklonální protilátky; lidé; Multiple Myeloma; Antibodies, Monoclonal, Humanized; oligopeptidy; mnohočetný myelom; chromozomální aberace; dexamethason; Chromosome Aberrations; Dexamethasone; Antineoplastic Combined Chemotherapy Protocols; Humans